Pengaruh Metode Tanya Jawab Terhadap Prestasi Belajar Siswa Mata Pelajaran Aqidah Akhlaq Kelas IV Di Madrasah Ibtidaiyah Muhammadiyah 06 Brondong Lamongan - Maftuhah; M. Chotibuddin; Aaisah Arsae; Anang Ma'ruf; Shintia Mafazatin (STIT Muhammadiyah Paciran, 2022)
This study aims to determine the application of the question and answermethod and how it affects student achievement in the fourth grade Akidah Akhlaq subjects atMI Muhammadiyah 06 Brondong Lamongan. This research uses descriptive quantitativeresearch. The subjects in this study were 50 students. By using the instrument in the researchis a questionnaire, observation and documentation.The results showed that the value of the coefficient of r arithmetic on r table with the numberof N = 50 for a significant level of 0.279 or 5%, then r count = 9.440 > r table = 0.279 andfor a significant level of 0.361 or 1% then r count = 9.440 > r table = 0.361 thus r count isgreater than r table. Then it can be said that Ho is rejected and Ha is accepted.